Factors related to sedentary behavior of pregnant women during the second/third trimester: prospective results from the large-scale Japan Environment and Children's Study - Makie Nagai; Akiko Tsuchida; Kenta Matsumura; Haruka Kasamatsu; Hidekuni Inadera; the Japan Environment and Children's Study Group (BMC, 2024)
Abstract Background Prolonged sedentary behavior in pregnant women is reported to be associated with worse health-related indices and pregnancy outcomes. The aim of this study was to identify relevant factors that can be targeted in interventions to reduce sedentary behavior during pregnancy. Methods Of 103,057 pregnancies registered in the Japan Environment and Children's Study, 83,733 pregnant women were included for analysis after excluding multiple enrollments, nonresponses, and missing outcome data. Data were collected using the International Physical Activity Questionnaire and analyzed using logistic regression models to calculate crude and adjusted odds ratios. Missing data were handled using multiple imputations, and statistical analyses were performed using SAS software. Results Mean sedentary behavior time increased from 5.4 h/day before pregnancy to 5.9 h/day during pregnancy. The percentage of women classified in the high sedentary behavior group increased from 25.6% before pregnancy to 31.2% during pregnancy. Factors associated with high sedentary behavior during pregnancy included longer hours spent watching television and playing video games before pregnancy, higher annual household income, and working status during pregnancy. Possible protective factors against high sedentary behavior included engaging in ≥ 150 min of moderate to vigorous physical activity per week before pregnancy. Conclusions This large-scale cohort study provides valuable insights into sedentary behavior patterns among pregnant women in Japan. To reduce the amount of time engaged in sedentary behavior during pregnancy, the planning and management of time spent watching TV and playing video games as well as establishing exercise habits before pregnancy are recommended.